Irrationality measures for certain q-mathematical constants - Bundschuh, Peter; Zudilin, Wadim (MATHEMATICA SCANDINAVICA, 2007)
We prove sharp irrationality measures for a q-analogue of π and related q-series, and indicate open problems on linear and algebraic independence of the series that might be viewed as q-analogues of some classical mathematical constants.